Pemanfaatan Limbah Berserat Dalam Konsentrat Untuk Sapi Jantan Umur Satu Tahun - S.N.O. Suwandyastuti; Efka Aris Rimbawanto (Agricultural Faculty, 2011)
The utilization of fibrous waste in concentrate for yearling male cattleABSTRACT. A series of experiment had been conducted to improved the quality of rice straw, rice bran and cassava solid waste through biological pretreatment using several species of microbes. Based on the digestibility and the fermentation product, indicated that 30 percent of rice straw, 35 percent of rice bran and 35 percent of cassava solid waste was the optimal ratio for concentrate formulated. The present experiment was carried out by experimental method with Completely Randomized Design, on twelve yearling male cattle of Ongole grade. The treatment tested were 3 physical form of the concentrate : (1) unfermented mesh; (2) fermented mesh and (3) fermented pellet. The variables measured were : energy and protein digestibility, rumen fermentation product, nitrogen balance and daily body weight gain. The digestion and balance trial were carried out by the Total Collection Method. The analysis of covariance shown, that there were significantly effects of the treatment tested whether upon the protein and energy digestibility, the nitrogen balance (P0.01), nitrogen ammonia production and daily body weight gain (P0.05), but there was no significantly effect on the Total Volatile Fatty Acid and the proportion of the individual VFA (P0.05). Based on the all variables measured, it was indicated that fermented pellet was the best concentrate (composed by 30% of fermented rice straw, 35% of fermented rice brand and 35% of fermented cassava solid waste).